Faktor-Faktor yang Mempengaruhi Kebakaran Hutan dan Lahan dalam Bingkai Media untuk Mitigasi Bencana Kedepan - Rosalina Kumalawati; Astinana Yuliarti; Meldia Septiana; Syaifuddin; Karnanto Murliawan; Rizky Nurita Anggraeni (Jurnal Ilmu Kehutanan, 2022)
Forest and land fires were national and international disasters that caused crucial environmental problems and were a local and global concern. This research was conducted to determine the factors that affected forest and land fires in the media frame for future disaster mitigation in addition to the existing restoration efforts such as rewetting, revegetation, and community economic revitalization to minimize its impact. Data were collected from 2012 to 2021 through the framing method and analyzed using content analysis. The results showed that the factors affecting forest and land fires from September 2019 to June 2021 were associated with human activity and natural events. The dominant human activities were land preparation for agriculture and settlements, illegal logging, and lack of public awareness. Meanwhile, the natural factors were the dry season, lightning strikes, and areas with less intensive management, such as non-residential areas.